Synthetic Aminoindanes: A Summary of Existing Knowledge - Pinterova, Nikola; Horsley, Rachel R.; Palenicek, Tomas (Frontiers in Psychiatry, 2017)
Objectives: Aminoindanes (“bath salts”, a class of novel psychoactive substances, NPSs) increased rapidly in popularity on the recreational drug market, particularly after mephedrone and other synthetic cathinones were banned in the UK in 2010. Novel aminoindanes continue to emerge, but relatively little is known about their effects and risks. Their history, chemistry, pharmacology, behavioural effects, pharmacokinetics and toxicity are reviewed in this paper. Methods: Scientific literature was searched on ISI Web of Knowledge: Web of Science (WoS) during June and July 2017, using English language terms: aminoindane, MDAI, 5,6-methylenedioxy-2-aminoindane, 5-IAI, 5-Iodo-2-aminoindane, 2-aminoindane, MDMAI, 5,6-Methylenedioxy-N-methyl-2-aminoindane, MMAI, 5-Methoxy-6-methyl-2-aminoindane. WoS was selected as it searches several databases simultaneously and has quality criteria for inclusion. For typical use and effects Erowid, PsychonautWiki, Bluelight and Drugs-Forum were searched; for legal status and epidemiology, the European Information System and Database on New Drugs (EDND) was used. Results: Aminoindanes were first synthesized for medical use as e.g., as anti-Parkinsonian drugs and later as a potential compound facilitating psychotherapy, however they are now widely substituted for ecstasy. Their mechanisms of action (primarily via serotonin), mean that they may pose a significant risk of serotonin syndrome at high doses, or when combined with other drugs. Fatally toxic effects have been observed both in the laboratory in animal studies and in clinic, where aminoindanes-related deaths have been reported. Conclusion: Greater knowledge about aminoindanes is urgently required to decrease risks of fatal intoxication, and appropriate legislation is needed to protect public health without impeding research.